Self-Acceptance of Young Prisoners in the Institute for Special Education for Children (LPKA) - Eflen Yuliarsih; Daharnis Daharnis; Yeni Karneli (Universitas Negeri Padang, 2020)
Adolescent inmates are a population that is vulnerable to depression because being a prisoner is a hard life for adolescents. All the pressure in prison will be a major cause of depression for juvenile prisoners while in detention. In addition, feelings of fear caused by public perceptions of free teenage inmates will make prisoners increasingly feel isolated. Therefore, to reduce these impacts, self-acceptance is needed. The purpose of this study is to describe the aspects of self-acceptance that exist in adolescent prisoners in prison. Samples were collected form 46 prisoners adolescents by applying the purposive sampling technique. The instruments used were self-acceptance questionnaires which has a reliability score of 0.934 (Alpha Cronbach).Data analysis used aquantitative approach with descriptive methods. The results of self-acceptance juvenile inmates obtained an average score of 155.93 (hight self-acceptance category) with an average percentage category of 70.88%.